Trauma sensitive schools: the roadmap of an experience of capacity building and certification in Portugal - Negrão, Mariana (2024)
Schools are a front-line institution, present in the life of every children and youth, and therefore can display a critical role in the provision of trauma sensitive care. In fact, the epidemiology of developmental trauma, and the recognition of its consequences for learning and development, demands a greater accessibility to trauma sensitive care that can reduce the risk of re-vitimization and other negative effects, contributing to protect children’s rights. This poster shares the roadmap for a program of capacity building and certification on trauma sensitive schools being developed and implemented in Portugal. This program, based on a whole school approach - which summons for the participation of school leaders, teachers, assistant staff and psychologists - is aimed at: a. spreading basic knowledge on trauma and trauma sensitive care provision amongst school communities; b. support the distinct roles of school staff in understanding and acting with students considering the effects of adversity and trauma in their life trajectories; c. promote change in schools policies and practices, fostering further alignments with the principles of trauma sensitive care. To fulfill these goals, the program comprises a. basic training activities targeting the elementary knowledge of all school staff; b. advanced training activities in particular themes (eg. mourning, domestic violence, staff self-care) available to school staff; c. regular supervision of a workgroup of professionals responsible for the revision of policies and practices within each school, adjusting them to a trauma sensitive context. All these activities are based on a first assessment of schools regarding their preparation and implementation of trauma sensitive care that encompasses training, policies and practices (for screening, assessment and trauma focused intervention), supervision and infrastructures. This project, pioneer in Portugal, is currently ongoing in a municipality in Northern Portugal and it involves 36 schools from kindergarten to secondary. Challenges of the implementation relate to the involvement of teachers and other staff in an area not immediately perceived as their territory and competence (mental health vs. teaching and education) and also considering low motivation and involvement of an aged working class, currently with many struggles related to their professional role. Strengths relate to the change of perspective regarding the effects of adversity and trauma accomplished by school staff that attended training and to the mobilization of school community (professionals but also reaching parents) in analyzing, discussing, and creating change in a culturally silenced topic. The poster intends to share and encourage trauma sensitive care in schools in other regions with similar challenges.